Pemikiran Ibnu Rusyd tentang Pendidikan dan Relevansinya pada Masa Kini - Lailatus Sarifah; Azka Al-Ghifari Akmal; Agus Gunawan; Iffan Ahmad Gufron (Journal on Education, 2025)
Islamic education is based on the Qur'an, Sunnah, the words, deeds and attitudes of the companions, philosophers, and ijtihad. Philosophers or philosophers are people who actively think critically and are involved in answering big questions that are difficult to solve. This paper examines the thoughts of Ibn Rushd, an Islamic philosopher. Ibn Rushd, Ibn Rushd was a 12th-century Islamic polymath known primarily for his contributions to philosophy, theology, medicine, astronomy, physics, psychology, mathematics, Islamic jurisprudence and law, and linguistics. His work has been used for educational purposes for centuries in both Islamic and Christian cultures. This study aims to determine the biographical background, life, and thoughts of Ibn Rushd on education, then to find the relevance of Ibn Rushd's educational thoughts to Islamic education in the modern era. The method used in compiling this paper is the library research method. Researchers collect data sources through text literature, both books, journals, and articles that are relevant to this discussion. The results of the study show that Ibn Rushd as a philosopher, expert in jurisprudence, medicine and also a legal expert. Ibn Rushd has ideas and thoughts related to education, that education is practical which must be assisted by a theoretically appropriate model so that practical implementation is always in accordance with its theoretical implementation which aims to provide correct knowledge so that it can be implemented into correct actions. Ibn Rushd's thoughts on education that are organized in objectives, curriculum, learning methods and teachers or educators are factors of the determinant elements in education. Therefore, Ibn Rushd's thoughts can be used as an important reference in the advancement of the world of education.